Facile fabrication of lightweight mullite fiber/phenolic ablator with low thermal conductivity via ambient pressure impregnation. Issue 19 (1st October 2021) - Jia, Xianfeng; Song, Wenda; Chen, Wei; Ma, Cheng; Wang, Jitong; Qiao, Wenming; Ling, Licheng
Abstract: A novel lightweight mullite fiber/phenolic ablator is readily fabricated using mullite fiber felt as the substrate and phenolic aerogel as the matrix via ambient pressure impregnation, sol-gel reaction and ambient pressure drying. The phenolic aerogel with a large amount of macropore can be well-embedded into the voids of flexible mullite fiber felt and form a superior interfacial interaction. The as-prepared mullite fiber/phenolic ablator has a low density of 0.30–0.33 g/cm 3 and a relatively high bending strength of 3.4–13.6 MPa. Compared to conventional ablative materials, the mullite fiber/phenolic ablator shows a much lower thermal conductivity of 0.036–0.039 W/(m·K) at room temperature. Moreover, the obtained ablator with linear ablation rate as low as 0.031 mm/s, exhibits excellent ablation resistance and thermal insulation in oxyacetylene flame simulated high temperature of 2000 °C.